HUBUNGAN ANTARA PERKEMBANGAN SASTRA DAN PERUBAHAN SEJARAH SOSIAL DI ERA REFORMASI - Mai Rahayu (Journal of Linguistics, Literature, Culture and History, 2025)
Literature plays a crucial role in reflecting social life and history, as it records and depicts various aspects of human life, including values, traditions, norms, experiences, and social conflicts within a society. This study aims to understand the interaction between socio-political dynamics and contemporary literary expression. This research uses a descriptive qualitative approach with content analysis methods to examine the content, themes, and socio-cultural context of literary works produced during the Reformation era in Indonesia. The Reformation era in Indonesia since 1998 has had a significant impact on various aspects of life, including literature and social history. Literature during this period was marked by greater freedom of expression, allowing writers to address previously restricted social and political themes.